Impact of Ground Motion Selection on The Seismic Assessment of Reinforced Concrete Buildings - Alshaheen, Ammar; Aljassim, Samir (Iraqi Journal of Civil Engineering, 2022)
The goal of this study is to determine the impact of ground motion recordings (GMs) selection on the seismic performance evaluation of reinforced concrete (RC) structures. From three GMs in ASCE7-10 to eleven GMs in ASCE7-16, the ASCE7 has upgraded the minimum GMs utilized in seismic analysis, When the GMs are used to evaluate an existing structure, the earthquake load may under or overestimate the structure's capacity. The case study is an existing RC building, dual system, and unsymmetric in-plane and height. Because of these asymmetries, the Non-linear Time History Analysis (NTHA) is the most accurate method. It is performed for 30 GMs in directions X and Y. The GMs were chosen and scaled to meet the Basrah city response spectrum curve (RSC), which is based on the existing Iraqi seismic code. The study parameters that were investigated are included story implication ratio, torsional irregularity index, floor rotation angle, and plastic hinge formation. These parameters are investigated in three cases. The selection of GMs for Case 1 and 2 are based on the ASCE7-10 while Case 3 is based on ASCE7-16. The comparison between cases is shown a considerable difference in structural response could lead to various retrofitting decisions. The findings revealed that existing RC buildings constructed in accordance with ASCE7-10, particularly medium and high-rise structures, should be re-evaluated